Multifunctional aspects of Piriformospora indica in plant endosymbiosis. Issue 3 (3rd July 2019) - S, Jisha; Kk, Sabu; S, Manjula
ABSTRACT: Piriformospora indica: (Hymenomycetes, Basidiomycota) is an endophytic fungus that colonises plant roots, and was originally isolated from Rajasthan desert. It is comparable to Arbuscular Mycorrhizal (AM) fungi in terms of plant growth promotional effects. P. indica has been used as an ideal example to analyse the mechanisms of mutualistic symbiosis. Major benefit of P. indica over AM fungi is that it is axenically cultivable in different synthetic and complex media. A preliminary attempt was made to scrutinise the role of P. indica co-cultivation on seedling vigour of common vegetables like Cucumis sativus L., Abelmoschus esculentus (L.) Moench, Solanum melongena L. and Capsicum annuum L. The positive effect of P. indica co-culture on seedling performance was compared to the effects of growth hormones like indole acetic acid and benzyl amino purine when supplemented to the MS medium at a concentration of 0.1 mg ml −1 . An exogenous supply of auxin resulted in enhanced production of roots and cytokinin supplement favoured shoot production, whereas P. indica co-culture favoured simultaneous production of shoot and root over the control. P. indica colonisation inside the roots of C. sativus L. was also successfully established. These preliminary results indicate the prospective role of P. indica in vegetable farming through its favourable effect on plant growth.